Cerebral Perfusion Monitoring Using Near-Infrared Spectroscopy During Head-Up Tilt Table Test in Patients With Orthostatic Intolerance - Kim, Yoo Hwan; Paik, Seung-ho; V, Zephaniah Phillips; Jeon, Nam-Joon; Kim, Byung-Jo; Kim, Beop-Min (Frontiers in Human Neuroscience, 2019)
The head-up tilt table test (HUT) is one of the primary clinical examinations for evaluating orthostatic intolerance (OI). HUT can be divided into three phases: dynamic tilt phase (supine to tilt up), static tilt phase (remain tilted at 70°), and post tilt phase (tilt down back to supine position). Commonly, blood pressure (BP) and heart rate (HR) are monitored to observe for OI symptoms, but are indirect measurements of cerebral perfusion and can lead to inaccurate HUT evaluation. In this study, we implemented a 108-channel near-infrared spectroscopy (NIRS) probe to characterize HUT performance by monitoring cerebral hemodynamic changes for healthy controls (HCs), OI patients with normal HUT results, and OI patients with positive HUT results: vasovagal syncope (VS), postural orthostatic tachycardia syndrome (POTS), orthostatic hypotension (OH), and orthostatic hypertension (OHT). By the end of the static tilt phase, OI patients typically did not show a complete recovery back to baseline cerebral oxygenation and total blood volume compared to HCs. We characterized the return to cerebral homeostasis by polynomial fitting total blood volume changes and determining the inflection point. The OI patients with normal HUT results, VS, OH, or OHT showed a delay in the return to cerebral homeostasis compared to the HC group during HUT.